2019
DOI: 10.3329/bhj.v34i2.44442
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Non-Communicable Diseases among the Admitted Patients in a District Level Hospital of Bangladesh

Abstract: Background: Non-communicable Diseases (NCD), particularly cardiovascular diseases, cancer, diabetes and chronic respiratory disease, have emerged as the leading threat to mankind worldwide. Likewise in Bangladesh, an increasing trend of incidence of NCDs has been observed and already they have become major public health concern. Hence, we aimed to study the pattern of NCDs among the admitted patients at an Upazila Health Complex (UHC) in Bangladesh. Methods: In this retrospective study, data of in-hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…10 Although communicable diseases were more prevalent in the last century but recently, noncommunicable diseases are the cause of six out of seven deaths in the developed world and half of all deaths in the developing world. 11,12 This trend had also been reported in previous studies and has been attributed to transition in epidemiology and lifestyles. 13,14 WHO predicts that non communicable deaths are expected to increase by 17% worldwide between 2010 and 2020.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…10 Although communicable diseases were more prevalent in the last century but recently, noncommunicable diseases are the cause of six out of seven deaths in the developed world and half of all deaths in the developing world. 11,12 This trend had also been reported in previous studies and has been attributed to transition in epidemiology and lifestyles. 13,14 WHO predicts that non communicable deaths are expected to increase by 17% worldwide between 2010 and 2020.…”
Section: Introductionsupporting
confidence: 82%
“…This is the most preferred method for disease prevention in a pragmatic way. 4,16 Unfortunately, in Pakistan, data on the treatment outcomes of hospital admissions are either unavailable or incomplete. Therefore, it is essential to assess these patterns with this study to provide a tool for better planning and appropriate management of prevalent diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, the burden of hospitalisation due to NCDs among the elderly are showing a rising trend globally as well as in India (Pandey et al , 2017a; Rahman et al , 2019). Our finding showed that young-old and elderly females were more hospitalised due to NCDs, so as in other studies (Kaur et al , 2019; Pandey et al , 2017a); conversely, earlier research has also found that elderly males have higher hospitalisations due to NCDs (Rahman et al , 2019). The elderly in the Northern region have the highest hospitalisations due to NCDs, which were also seen in past research (Kaur et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence rate of hospitalization in our study was 175 per 10,000 population, with higher hospitalization rates due to NCDs rather than communicable diseases. A study also reported higher self-reported incidence of NCDs in rural Bangladesh than communicable diseases [ 8 ] and hospitalizations at the district level hospitals were also found to be comparatively higher for NCDs than communicable diseases [ 27 ]. Similarly, a study in India (a neighboring country) also found that hospitalization rates for NCDs and injuries are slightly higher in India than communicable diseases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%